Measuring IHDI in Indonesia and How The Impact of Investment and Government Expenditure - Achmad Fadlil Abidillah; Rosida Dwi Ayuningtyas; Mohammadtahir Cheumar (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2022)
This research aims to measure Indonesia's Islamic Human Development Index (IHDI) and analyze the effect of domestic investment, foreign direct investment, and government expenditure on Indonesia's IHDI. IHDI is measured by calculating five indicators which are derivatives of maqashid sharia, namely the religion index, life index, family index, science index, and wealth index. Meanwhile, the analytical tool used to determine the effect of domestic investment, foreign direct investment, and government expenditure on IHDI is panel data regression. Observations were made in 34 provinces in Indonesia from 2015 to 2019. IHDI calculations show that Special DI Yogyakarta, North Kalimantan, Riau Islands, East Kalimantan, and DKI Jakarta are the top five provinces with the highest IHDI. Meanwhile, North Sumatra, Papua, East Java, South Sumatra, and East Nusa Tenggara are the five provinces with the lowest IHDI. The regression analysis results show that the IHDI in Indonesia is positively influenced by domestic investment and government expenditure, while foreign direct investment does not affect the IHDI in Indonesia.